Role of CaF2on mechanochemically synthesized leucite as dental veneering glass ceramics - Kumar P.H.; Srivastava A.; Kumar V.; Singh H.; Sharma S.; Singh V.K. (My University, 2025)
Leucite based glass ceramic is widely used in dental ceramics as porcelain fused to metals for veneering applications. Main properties considered here are high coefficient of thermal expansion and good mechanical properties. Owing to these requirements, high expansion phase such as leucite is incorporated in these glass ceramics. The present work was aimed to synthesise leucite using its stoichiometric batch compositions and subsequent high energy ball milling. CaF2 was also added in another mix to study its role on leucite formation. Further prepared, leucite phase was added in separately prepared low temperature glass frit powders to control amount of glass and leucite content. X-ray diffraction results displayed that high energy ball milling and additive promoted the formation of leucite as a major crystalline phase. Furthermore, CaF2 also suppressed the subsidiary crystallisation of kalsilite phase. Evaluated average coefficient of thermal expansion in the temperature range of 20-500°C was very close to the theoretical value of pure leucite. © 2015 Institute of Materials, Minerals and Mining